Physical Oceanography Developments Since 1950 - Jochum, Markus; Murtugudde, Raghu (Springer New York : Imprint: Springer, 2006)
Over the last five decades physical oceanography developed rapidly from a branch of fluid dynamics, with only a few observations, to a mature science with global field programs, large computer resources, and a complex theoretical framework. Today understanding of ice ages, global warming, or predictions of El Niño are to a large extent due to progress in understanding ocean physics. Therefore, it is important that the history of physical oceanography is made known so that citizens can understand the current state of climate sciences and policy makers can make informed decisions about future research. This volume contains a historical introduction by Bruce Warren and twelve historical perspectives from world-renowned physical oceanographers.